Fiscal Consolidation How Much, How Fast and by What Means? - Sutherland, Douglas (OECD Economic Policy Papers, 2012)
The economic and financial crisis was the catalyst for a fiscal crisis that engulfs many OECD countries. Consolidating public finances in order to address the consequences of the crisis, underlying weaknesses and also future spending pressures creates important challenges. Fiscal consolidation requires choices to be made about how much consolidation is needed, how fast it should be implemented and which instruments should be used. Estimates of fiscal gaps suggest that substantial and sustained fiscal tightening will be needed in nearly all countries to bring debt down to prudent levels. However, given a weak global economy, implementing a large fiscal tightening could be particularly costly. Structuring consolidation packages to use instruments with low multipliers initially and enhancing the institutional framework for fiscal policy to lend greater credibility to the commitment to consolidate over time may help minimise the trade-offs with growth in the short run. In most countries there is scope to target spending programmes more effectively and eliminate distortions in taxation. Such measures, buttressed by structural reforms, such as to unsustainable pension systems, can underpin fiscal sustainability, while minimising the costs to long-run growth